Struktur Komunitas Makrozoobenthos Pada Daerah Pasang Surut Di Zona Pemanfaatan Taman Hutan Raya Ngurah Rai (Tahura), Desa Pemogan, Denpasar - Setiawati, Putu Eva; Dharma, I Gusti Bagus Sila; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023)DO - 10.24843/jmas.2023.v09.i02.p03, 2023)
The mangrove ecosystem lives along the coast and influenced by tidally process. The mangrove ecosystem has many functions and associated with different types of biota, one of them is macrozoobenthos. Macrozoobenthos is organism that live at the bottom of the substrate. This study aims to determine the community structure of macrozoobenthos and the influence of physic-chemical sediments parameters (temperature, salinity, pH nitrates and phosphates) of the abudance of macrozoobenthos in the Using Zone Taman Hutan Raya (Tahura) Ngurah Rai, Pemogan Village, Denpasar. Data analysis using by Bray Curtis index to see the similarity between the stations and Principal Component Analysis (PCA) to see the parameters that influence the abundance of macrozoobenthos. Result showed that the diversity index of macrozoobenthos is low - medium, Eveness index is low - high and Dominance index is medium-high. The highest similarity is between station 3 and 4, while station 1 has no similarity with other. PCA analysis showed that abundance of macrozoobenthos was influenced by temperature, salinity, nitrate, and phosphate.
Keywords: Mangrove, Makrozoobenthos, Zona pemanfaatan